1994
DOI: 10.1038/jcbfm.1994.109
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Dependence of Cerebral Blood Flow on Blood Viscosity after Blood Exchange with a Newtonian O2 Carrier

Abstract: Whether the increase in cerebral blood flow measured after hemodilution is mediated by a decrease in blood viscosity or in oxygen delivery to the brain is debated. In the present study, blood was replaced by an oxygen-carrying blood substitute, ultrapurified, polymerized, bovine hemoglobin (UPBHB). In contrast to normal blood, UPBHB yields a constant and defined viscosity in the brain circulation, since its viscosity is not dependent on the shear rate. CBF was determined after blood exchange with UPBHB in one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 18 publications
6
42
3
Order By: Relevance
“…Haemodilution will reduce the red cell mass resulting in improvement of microcirculation in many organs including the brain [1,22,30]. The increased CBF after haemodilution seems to be the result of the compensation for decreased arterial O 2 content and not to be related to decreased blood viscosity [7,31,39]. Therefore, determination of the blood viscosity in our patients was considered unnecessary.…”
Section: Discussionmentioning
confidence: 81%
“…Haemodilution will reduce the red cell mass resulting in improvement of microcirculation in many organs including the brain [1,22,30]. The increased CBF after haemodilution seems to be the result of the compensation for decreased arterial O 2 content and not to be related to decreased blood viscosity [7,31,39]. Therefore, determination of the blood viscosity in our patients was considered unnecessary.…”
Section: Discussionmentioning
confidence: 81%
“…Our laboratory (6,39) showed that the reduction of FCD found after decreasing systemic Hct to 18% of baseline with low-viscosity plasma expanders was not decreased further by continuing hemodilution with high-viscosity plasma expanders. Waschke et al (43) found that cerebral perfusion was not changed when blood was replaced with fluids with the same oxygen-carrying capacity and viscosities varying from 1.4 to 7.7 cP. Krieter et al (21) increased plasma viscosity using dextran 500 kDa and found that medians in tissue PO 2 in skeletal muscle were maximal at 3 cP of plasma viscosity and that there were no changes in tissue oxygenation and organ perfusion when blood was he- Calculations of global oxygen transport are not directly measurable in our model.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [21] elevated plasma viscosity four-fold (4 cP), finding vasodilation and reduction of vascular hindrance in several vital organs. Waschke et al [22] found unchanged cerebral perfusion when blood was replaced with fluids with the same oxygen-carrying capacity and viscosities varying from 1.4 to 7.7 cP. Krieter et al [23] infused dextran (500 kDa) and found maximal tissue p O 2 in skeletal muscle and liver at plasma viscosities of 3 and 2 cP, respectively.…”
Section: Blood Viscosity Hemodilution and Plasma Expansionmentioning
confidence: 97%